Self-Instrusction Sebagai Teknik Alternatif Meningkatkan Kepercayaan Diri (Overt-Covert) Siswa SMP - Susanti, Romia Hari (Universitas Nusantara PGRI Kediri, 2020)
Poor self-concept in adolescents, one of which can be seen from the lack of self-confidence. The student who has confidence will be certain in their abilities and have realistic expectations, and when expectations do not materialize, they still think positively and can receive it. Unrealistic expectations can be reduced by using techniques that can direct students to control negative cognitive behaviors and thoughts that cause low student confidence (overt-covert). Wilcoxon test analysis results show that sig. (2-tailed) 0.042 <0.05 which can be interpreted as a technique of self-instruction can increase the confidence of students of SMP Muhammadiyah 4 Singosari, with a significant level of 5%. The use of self-instruction techniques as an alternative technique to increase student confidence starts from rational procedures, self-guidance, overt external guidance, overt self-guidance, faded overt self-guidance, covert self-guidance, and homework.